Rethinking trade and trade policy: Gomory, Baumol, and Samuelson on comparative advantage - Thomas I. Palley (Levy Economics Institute of Bard College, 2006)
The theory of comparative advantage says that there are gains from trade for the global economy as a whole. In this second brief of a three-part study of the international economy, Research Associate Thomas Palley observes that comparative advantage is driven by technology, which can be influenced by human action and policy. These associations have huge implications for the distribution of gains from trade and raise concerns about the future impact of international trade on the US economy. Palley calls for strategically designed US trade policy that can influence the nature of the global equilibrium and change the distribution of gains from trade. Recent works by Ralph Gomory and William Baumol and Paul Samuelson use pure trade theory to question the distribution of trade gains across countries over time and to challenge commonly held beliefs. These microeconomic and trade theorists identify a new issue: the dynamic evolution of comparative advantage and its impact on the distribution of gains from trade, which depends on changing global demand and supply conditions. (See also, Public Policy Brief No. 85.)
Keywords: 330; Außenwirtschaftstheorie; Außenwirtschaftspolitik; Komparativer Kostenvorteil; Dogmengeschichte; Theorie